2015
DOI: 10.1002/cben.201500025
|View full text |Cite
|
Sign up to set email alerts
|

Modular Equipment for Chemical Process Development and Small‐Scale Production in Multipurpose Plants

Abstract: Small‐scale, continuous‐flow processes are currently discussed in the chemical industry for rapid process development and manufacturing of small product amounts. This contribution describes an equipment toolbox system for continuously operated chemical reactors consisting of microfluidic chip or plate reactors for rapid mixing, capillary or coil tube reactors for defined mixing and residence time, as well as continuously stirred tank reactors. The involved phases of the physico‐chemical system determine the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 46 publications
0
24
0
1
Order By: Relevance
“…The design space diagram is applicable for larger flow rates as well. Therefore, scaleup to pilot or production scale can be facilitated while flow characteristics, e.g., RTD, can be maintained [12,39].…”
Section: Equipment Design Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The design space diagram is applicable for larger flow rates as well. Therefore, scaleup to pilot or production scale can be facilitated while flow characteristics, e.g., RTD, can be maintained [12,39].…”
Section: Equipment Design Proceduresmentioning
confidence: 99%
“…For upstream operation, flexible equipment toolboxes and platform solutions [11,12] are available for process development in laboratory and scale-up to production capacity [13,14]. Due to their small dimensions and high specific surface area, microreactors proved superior performance for various single and multiphase applications [15].…”
Section: Introductionmentioning
confidence: 99%
“…The reactor toolbox with mixing elements on a plate (with channel), (coiled) tube, vessel (and enlarged to column), adapted from .…”
Section: Concise Historical Development Of Chemical Equipmentmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Some reviews have also been reported concerning effective mixing in microchannels 34,35 and in small-scale production. 36 In the present study, we investigated the behavior of emulsion droplets in a capillary EMP system, and observed a forced coalescence of emulsion droplets, an alignment of larger droplets with regular intervals and an interactive circulation of smaller droplets around larger droplets in a capillary. The cause of the interesting phenomena observed in the present study was discussed in terms of the local current density around a droplet, which was evaluated by conventional simulation software.…”
Section: Introductionmentioning
confidence: 96%